Canadian LNG competitiveness - Findlay, P (Oxford Institute for Energy Studies, 2019)
In the first half of this decade now coming to an end, Canada was a desirable hotspot for LNG proponents — over 20 liquefaction projects were proposed, primarily off Canada’s West Coast in the province of British Columbia, driven by supermajors, North American midstream operators, Asian national oil companies, and Asian consumers. Since that time, investor interest in Canadian projects has waned and only the 13 mtpa LNG Canada plant has been sanctioned; the plant includes a yet unsanctioned 13 mtpa expansion option. Other projects faltered and shuttered due to concerns about escalating costs in remote areas, regulatory uncertainty, activist fervor, and tepid government support. Meanwhile, despite starting from behind with an overall higher cost of feedgas and much greater shipping distances to Asia, the US Gulf Coast has attracted a deluge of sanctioned (and ready to be sanctioned) LNG investment. Developments in Russia and Africa have also leapfrogged most Canadian project proponents to reach final investment decisions on world-scale projects. Global competition to supply the projected LNG demand growth is fierce. This paper examines how Canada stacks up against other exporting countries: how Canadian LNG competes on cost; available LNG business models; security of supply; environmental, social and governance (ESG) considerations; and the likelihood of getting a project approved and built — this last factor is where Canada seems to be frustrating, if not undermining its own LNG prospects.